Anticoagulation Therapy for Non-valvular Atrial Fibrillation: A Mini-Review - Wu, Jia; Zhang, Yonggang; Liao, Xiaoyang; Lei, Yi (Frontiers in Medicine, 2020)
Anticoagulation therapy is an important method of preventing stroke in individuals with atrial fibrillation (AF). Atrial fibrillation is a quivering or irregular heartbeat that can lead to blood clots, stroke, heart failure and other heart-related complications. Clinical guidelines on AF consistently recommend long-term oral warfarin to treat valvular atrial fibrillation (VAF). However, due to varying risks of blood clots and stroke associated with different types of non-valvular atrial fibrillation NVAF, it is unclear whether direct oral anticoagulant (DOAC) can replace warfarin. Despite a recent increase in evidence on the effectiveness and the importance of anticoagulant therapy in preventing thromboembolic events associated with NVAF, clinical prevention strategies remain complex. Given the complexities associated with clinical use of anticoagulants for patients with NVAF, this review aims to offer guidance on patient anticoagulant use based on current available evidence.